Ultras Ahlawy and the Spectacle: Subjects, Resistance and Organized Football Fandom in Egypt - Ibraheem, Dalia Abdelhameed (AUC Knowledge Fountain, 2015)
This thesis focuses on organized football fandom groups in Egypt (namely the Ultras Ahlawy- UA07) and how the individual fan is constructed and disciplined in this collective, particularly in the urban settings of Cairo. I examine the Ultras through various lenses. Firstly, the research discusses how the Ultras fans perceive nationalism, how they relate their love to the club to their love of the country and the role of nationalism in creating an imagined community of al-Ahly supporters. Second, I engage in this male exclusive group by tracing how the game is socialized as a masculine game, how the young boys are introduced to the game, the gender dynamics in the group and the fraternity between the group’s individuals. Third, I portray the different performances, graffiti, and ritual practices among the football fans. The making of the political subject and his agency by focusing on the Ultras involvement with the revolution is the fourth lens through which I explore the Ultras. Finally, the thesis discusses how through the Ultras, these organized fans reset their relation to the city through their space making practices in their neighborhoods, in the stadium, in the club, and in different sites where they congregate.